Lima principles : freedom of expression and access to state held information (Consejo de la Prensa Peruana LimaPE, 2001)
Sets out 10 general principles which deal with the following topics: access to information as an individual right; access to information; transparency and development; the authorities' obligations; journalism and access to information; protection of journalist's sources; legislation on access to information; exceptions to the right of access to information; protection of whistleblowers; and, legal protection of the right of access to information
Keywords: FREEDOM OF SPEECH